2020
DOI: 10.3389/fphar.2020.00068
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Metabolomics for Identification of Metabolic Pathways and Deciphering the Effect Mechanism of Dioscin on Rectal Cancer From Cell Metabolic Profiles Coupled With Chemometrics Analysis

Abstract: High-throughput liquid chromatography-mass spectrometry (LC-MS)-based metabolomics can provide the holistic analysis of the low molecular weight endogenous metabolites in cells and reflect the changes of cellular regulation and metabolic pathways. Our study designed to reveal the potentially pharmacological effects of dioscin on SW480 rectal cancer cells using nontargeted metabolomics method to probe into small molecular metabolites and pathway changes. After the cell assay of proliferation, apoptosis, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The in vivo reduction in the activities of Kreb's cycle in infarcted hearts may represent at an early maladaptive phase in the metabolic alterations after MI (24). It has been reported that highthroughput liquid chromatography-mass spectrometry (LC-MS)-based metabolomics demonstrate that dioscin could be associated with gluconeogenesis, Kreb's cycle, and butanoate metabolism (24). Consistently with the previous results, we further confirmed that dioscin is involved with Kreb's cycle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The in vivo reduction in the activities of Kreb's cycle in infarcted hearts may represent at an early maladaptive phase in the metabolic alterations after MI (24). It has been reported that highthroughput liquid chromatography-mass spectrometry (LC-MS)-based metabolomics demonstrate that dioscin could be associated with gluconeogenesis, Kreb's cycle, and butanoate metabolism (24). Consistently with the previous results, we further confirmed that dioscin is involved with Kreb's cycle.…”
Section: Discussionsupporting
confidence: 90%
“…The selective accumulation of the citric acid cycle intermediate succinate is a typical metabolic issue after infarction in a range of tissues, responsible for the accumulation of mitochondrial ROS production after reperfusion (23). The in vivo reduction in the activities of Kreb's cycle in infarcted hearts may represent at an early maladaptive phase in the metabolic alterations after MI (24). It has been reported that highthroughput liquid chromatography-mass spectrometry (LC-MS)-based metabolomics demonstrate that dioscin could be associated with gluconeogenesis, Kreb's cycle, and butanoate metabolism (24).…”
Section: Discussionmentioning
confidence: 99%
“…The pellets corresponding to around 10 7 cells were resuspended in 300 μL of cold methanol and disrupted with an ultrasonic probe (16 burst of 0.5 s per pulse at 80% intensity). After centrifugation at 15,000 × g , 15 min, 100 μL of the supernatant was transferred to a new tube and evaporated to dryness in a SpeedVac ( Wang et al, 2020 ). The metabolite extracts were re-suspended in 0.1 mol L −1 formic acid containing 0.2 mmol L −1 methionine sulfone (internal standard) by 1 min vortex mixing and then centrifuged (15,000 × g , 15 min).…”
Section: Methodsmentioning
confidence: 99%
“…involved in intermediary metabolism and whose levels are related to genetic expression (Figure 1). Metabolome reflects changes in enzyme activities, alteration in signalling pathways, catabolic and synthetic reactions [14].…”
Section: Metabolomics: An Indispensable Tool For Anticancer Drug Discovery From Plantsmentioning
confidence: 99%
“…involved in intermediary metabolism and whose levels are related to genetic expression (Figure 1). Metabolome reflects changes in enzyme activities, alteration in signalling pathways, catabolic and synthetic reactions [14]. The two main approaches in metabolomics are targeted (biased) and untargeted (unbiased) metabolite profiling.…”
Section: Metabolomics: An Indispensable Tool For Anticancer Drug Discovery From Plantsmentioning
confidence: 99%